Analisis Kesulitan Belajar Siswa pada Materi Perkalian di Sekolah Dasar - Salsabilah Bilah; Khairunnisa Khairunnisa; Eltrian Eltrian; Ni Putu Puspita Rohmaningsih; Reva Feybe Imanuela Mamusu (JURNAL DIKDAS, 2026)
This study aims to analyze the learning difficulties experienced by students in multiplication material at the elementary school level. Mastery of multiplication concepts is an essential competency in mathematics learning because it becomes the foundation for more advanced mathematical topics. However, in reality, many students still experience difficulties in understanding this concept. This research used a qualitative approach with a descriptive method. The subjects of this study were 18 fourth-grade students at SDN 19 Dampelas. Data were collected through observation, interviews, and analysis of students’ mathematics cognitive assessment documents. The results showed that students' understanding of multiplication material varied. Six students were able to understand the material well, five students had difficulties memorizing basic multiplication facts, and seven students experienced difficulties in understanding the concept of multiplication, especially in word problems and repeated addition forms. These difficulties were influenced by several factors, including the teaching methods used and the students' initial abilities. Therefore, more interactive and meaningful learning methods are needed to help students better understand multiplication concepts.